확장슬롯 적응형 SECS-LExpressnet 프로토콜의 성능 분석 - 유동관 (韓國컴퓨터情報學會論文誌, 2003)
In this Paper, an improved protocol is proposed by supplementing a control station for transmission cycle management and slot-extension function. This protocol is proposed to complement the shortcomings of the conventional L-Expressnet protocol which is used for round robin process in bus topology. We analyzed the improved protocol in channel utilization viewpoint and compared the result with that of the conventional Protocol. From this result, we showed that the channel utilization of the improved protocol is superior to that of the conventional protocol when a maximum normalized propagation delay is increased. 본 논문은 일반적인 버스 토포로지에서 라운드로빈 방식의 동작을 구현한 기존의 L-Expressnet 프로토콜이 채널이용률이 떨어지는 단점이 있어 이를 보완하고자 사이클 관리를 위한 컨트롤 스테이션과 슬롯 확장 기능을 적용시켜 성능을 개선시킨 다음에 이것의 성능을 기존의 방식들과 비교 분석하였다. 개선된 프로토콜의 성능 분석은 채널 이용률 관점에서 이루어졌으며 이것을 기존의 다른 프로토콜과 비교한 결과 컨트롤 스테이션과 슬롯확장 기능을 적용시킨 프로토콜이 기존의 여러 방식의 프로토콜보다 최대 정규화 전파지연 값이 커질 경우 더 나은 성능을 보임을 알 수 있었다.